Cross sections for the ionization of tetrahydrofuran by light ions. (July 2015) - Wang, Mingjie; Rudek, Benedikt; Buhr, Ticia; Bennett, Daniel; Hilgers, Gerhard; Rabus, Hans
Synopsis: Double differential cross sections (DDCS) for ionization of tetrahydrofuran by protons and helium ions were measured in the projectile energy range between 420 keV and 16.14 MeV at emission angles between 30° and 90° relative to the beam direction. The preliminary results for 420 keV protons indicate that the relative energy dependence of the experimental DDCS is in a better agreement with the modified Hansen-Kocbach-Stolterfoht (HKS) model [1] than with the recently reported calculation based on the dielectric response function (DRF) formalism [2].